FAKTOR YANG MEMPENGARUHI KINERJA DAN KINERJA SEBAGAI VARIABEL MEDIASI PENGARUH KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA DOSEN PERGURUAN TINGGI SWASTA DI MALANG - Fathorrahman Fathorrahman (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
This study aimed at test and analyze the effect of organizational commitment on the performance and working satisfaction as the mediatory variable. It was a causal / explanatory research. This research was conducted to identify the causal relationships among the available and clearly defined variables in the study problems through the hypothesis testing. The sample were 95 respondents, who were 95 lecturers of different private universities in Malang. The sampling technique in the research was multistage random sampling. The data were obtained through distribution and collection of questionnaires. They were then analyzed witht he structural model with GeSCA program. The results showed that 1) the motivation had a positive significant effect on the performance, 2) the ability had a positive significant effect on the performance, 3) the organizational commitment had a positive significant effect on the performance, 4) the organizational commitment had a positive significant effect on working satisfaction, 5) the performance had a positive significant on the working satisfaction, And 6) the Performance also gave mediatory support to organizational commitment on the working satisfaction.